Development of Equation for Predicting of Outdoor Thermal Comfort for Individuals During Nighttime in Tropical Humid Climate - Sangkertadi; Reny Syafriny (Mimbar Ilmu, 2023)
The sun's heat factor is the leading cause of discomfort when doing outdoor activities, which does not happen at night. However, it is also necessary to ensure that humans feel comfortable at night, even without sunlight. This study aims to develop a regression equation to predict the comfort scale of humans doing outdoor activities at night in humid tropical climates. This study applied a field research method involving 80 adult respondents consisting of 40 men and 40 women in an outdoor location in a humid tropical climate. The data collection method uses a questionnaire. Respondents as subjects were asked about their comfort level when they received local climate penetration that touched their bodies. At the same time, climate variables around the issue were measured. The climate measured consists of air temperature, radiation temperature, relative humidity, and air speed. The data analysis technique is quantitative descriptive. The research results found 2 regression equations, namely for the case of people sitting and walking casually. The regression equation was then validated by comparing it with other equations, namely PMV and PET. The regression equation from this study helps make decisions about facilities and outdoor space design that provide a sense of comfort for humans during the funeral.